Resistance Training to Failure: A Science-to-Practice Guide for the Fitness Professional. (March 2022) - Mang, Zachary; Rasinski, Katarina; Kravitz, Len
Abstract : Apply It!: In the case of both low- and high-intensity resistance training (RT), fitness professionals should teach their clients to lift near failure without achieving complete momentary muscular failure (MMF), as indicated by a ratings of perceived exertion value of 8 to 9 or repetitions in reserve value of 1 to 2. MMF and volitional interruption (VI) elicit comparable improvements in strength and hypertrophy at high intensities (75% to 85% 1RM), so both may be integrated into a single training session ( i.e., 4 sets of bench press, first three performed to VI, final set to MMF). Program failure training to align with your client's goals — performing RT sets to failure — may be more effective for hypertrophy, whereas nonfailure sets may be more beneficial for power. Abstract : Recent research that compares resistance training performed to failure and nonfailure with different intensities and tempos sheds light on how to effectively program failure sets to align with the individual training status and goals of each client.